Screening of Rice Varieties against Brown Leaf Spot Disease at Jyotinagar, Chitwan, Nepal - Magar, P. B. (International Journal of Applied Sciences and Biotechnology, 2015)
A field experiment was conducted on fourteen rice varieties to determine the level of resistance against brown leaf spot (Bipolaris oryzae)disease at Karma Research and Development Center, Jyotinagar, Chitwan during summer in 2013. Design used was randomized completeblock design with three replications. Disease severity, total AUDPC value, thousand grain weight and grain yield were highly significant amongthe rice varieties. Disease severity and total AUDPC value ranged from 21.73% to 58.07% and 614.8 to 1827 respectively. None of thesevarieties were found either resistant or highly resistant to disease. Only HJ-G1 and HJ-G2 were moderately resistant with grain yield of 5.10t/ha and 4.25 t/ha respectively. HJ-G1 variety had the highest grain yield 5.10 t/ha and lowest disease severity (21.73%) as well as total AUDPCvalue (6148). From this experiment, it can be concluded that HJ-G1 variety can be used for higher grain yield purpose under similar fieldcondition because it has highest yield and also tolerant to disease. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12014 Int J Appl Sci Biotechnol, Vol. 3(1): 56-60